2015
DOI: 10.1002/jmri.25140
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of skeletal age MR examination using compressed sensing

Abstract: These results demonstrate the validity and reliability of skeletal age examination accelerated by CS-MRI. We conclude that the acceleration factor of 3 was optimal. J. Magn. Reson. Imaging 2016;44:204-211.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The potential acceleration is markedly higher than acceleration factors reported in a recent study by Terada et al . reducing the acquisition time by a factor of 4 from 2:44 minutes to 41 seconds 42 . However, our results cannot easily be compared to the work of Terada et al ., since they used a low-field MR scanner at 0.3 Tesla.…”
Section: Discussionmentioning
confidence: 99%
“…The potential acceleration is markedly higher than acceleration factors reported in a recent study by Terada et al . reducing the acquisition time by a factor of 4 from 2:44 minutes to 41 seconds 42 . However, our results cannot easily be compared to the work of Terada et al ., since they used a low-field MR scanner at 0.3 Tesla.…”
Section: Discussionmentioning
confidence: 99%
“…A final limitation of the current study is MRI as image modality due to the high cost in comparison to X-ray due to spacious facilities, equipment, medical technical assistants, and examination duration. In [69][70][71][72][73][74][75][76][77][78], a solution is proposed to accelerate acquisition times by reconstructing MRIs using undersampled data in k-space. Besides reducing the costs it can lower the stress to patients as well, which is particularly useful for young refugees with traumatic backgrounds.…”
Section: Study Limitations and Practical Implementationmentioning
confidence: 99%
“…Besides reducing the costs it can lower the stress to patients as well, which is particularly useful for young refugees with traumatic backgrounds. First promising applications of the acceleration technique in the area of age estimation have been analyzed in [71,74,75]. Other non-invasive techniques such as ultrasound (US) have yet to be evaluated for their suitability for age estimation, especially when used in combination with machine learning.…”
Section: Study Limitations and Practical Implementationmentioning
confidence: 99%
“…Using compressed sensing with an open 3-T MR scanner, Terada et al demonstrated that suitable hand/wrist images were still obtained with a 55-s acquisition time. 69 Using a 3-T MR scanner, Neumayer et al presented a 4-minute approach to study the AGFAD triad of anatomical sites. 70 These results look promising but need to be validated before they can be generally applied.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%